IMPLEMENTASI KEGIATAN SHALAT DHUHA DALAM MEMBENTUK KARAKTER RELIGIUS SISWA KELAS I MADRASAH IBTIDAIYAH ICBB YOGYAKARTA - Anggreini, Sari; Hafiz, Khairil; Lestari, Sri Ulandari Puji; Ardani, Anisa Rahayu; Damayanti, Alif Fia; Isnain, Muhammad Fadil Nur; Ramadhani, Ninda Suci; Sulistyo, Agus (Jurnal Manajemen Pendidikan, 2025)
This study aims to describe the implementation of the shalat dhuha activity in shaping the religious character of first-grade students at Madrasah Ibtidaiyah Islamic Centre Bin Baz Yogyakarta. A descriptive qualitative approach was employed with first-grade teachers as the research subjects, using observation, in-depth interviews, and documentation as data collection techniques, while data analysis followed the Miles and Huberman model consisting of data reduction, display, and conclusion drawing. The findings indicate that shalat dhuha is performed collectively after the halaqah tahfidz through the talaqqi method in which the teacher guides the recitation and movements for students to imitate, fostering discipline, gratitude, and positive moral habits. Challenges such as limited focus and time constraints were addressed through strengthened supervision and schedule adjustments. The novelty of this study lies in its detailed description of integrating shalat dhuha as a routine instructional practice to cultivate early religious character formation, particularly through the effective application of the talaqqi method for lower-grade MI students.